2002
DOI: 10.1007/bf02573872
|View full text |Cite
|
Sign up to set email alerts
|

Deficient expression ofO 6-Methylguanine-DNA methyltransferase combined with mismatch-repair proteins hMLH1 and hMSH2 is related to poor prognosis in human biliary tract carcinoma

Abstract: Combined MGMT and MMR is a possible prognostic marker that probably reflects an accumulation of genetic mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 37 publications
2
37
0
2
Order By: Relevance
“…Tumors with nodal metastasis (N1-2) in the present study showed more frequent loss of MGMT expression than those without nodal metastasis (N0). The association of MGMT loss with nodal metastasis has also been reported in other human cancers, such as oral, bile duct, and gastric cancers (17,18). Previous reports underscored its potential as a candidate of predictive marker for nodal metastasis.…”
Section: Discussionmentioning
confidence: 71%
“…Tumors with nodal metastasis (N1-2) in the present study showed more frequent loss of MGMT expression than those without nodal metastasis (N0). The association of MGMT loss with nodal metastasis has also been reported in other human cancers, such as oral, bile duct, and gastric cancers (17,18). Previous reports underscored its potential as a candidate of predictive marker for nodal metastasis.…”
Section: Discussionmentioning
confidence: 71%
“…In CC, MGMT expression has been found to be a good prognostic indicator on univariate analysis (133). In a further study, methylation of the MGMT promoter (which closely correlated with decreased protein expression) was significantly associated with poor survival (134).…”
Section: Genetic Repairmentioning
confidence: 83%
“…On the other hand, loss of MGMT expression could also be a negative prognostic factor because of an increased susceptibility to acquiring other mutations (48 -50). Finally, it is important to keep in mind that hypermethylation can simultaneously occur in other genes with a CpG island in their promoter regions (51), making it more difficult to predict the final behavior of tumor cells.…”
Section: Discussionmentioning
confidence: 99%